2017
DOI: 10.1007/s10336-017-1497-9
|View full text |Cite
|
Sign up to set email alerts
|

The breeding performance of raptors in urban landscapes: a review and meta-analysis

Abstract: Global urbanisation is rapidly increasing and can have profound impacts on wild flora and fauna. For many species, the impacts are detrimental and irreversible, whereas others are able to colonise and apparently thrive in these novel, human-made environments. Raptors are particularly susceptible to changes in the environment due to their position at the end of the food chain, yet some species are increasingly associated with towns and cities. To explore the impact of urbanisation on raptors, we reviewed the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 98 publications
(196 reference statements)
1
74
0
1
Order By: Relevance
“…, Tomasevic and Marzluff , Kettel et al. ), with urban populations of insectivorous birds tending to have smaller clutches, and to produce fewer fledglings that have lower body mass compared to rural populations (Chamberlain et al. , Seress et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Tomasevic and Marzluff , Kettel et al. ), with urban populations of insectivorous birds tending to have smaller clutches, and to produce fewer fledglings that have lower body mass compared to rural populations (Chamberlain et al. , Seress et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several bird species lay earlier in urban areas, and it is hypothesized that in species that primarily feed their offspring with phytophagous insects earlier breeding is an adaptation to the earlier seasonal peaks in food availability in response to urban heat island effects (Vaugoyeau et al 2016). Although birds' reproductive success may be either increased, decreased, or not affected by urban development, this depends on the species' characteristics (Marzluff et al 2016, Tomasevic and Marzluff 2017, Kettel et al 2018, with urban populations of insectivorous birds tending to have smaller clutches, and to produce fewer fledglings that have lower body mass compared to rural populations (Chamberlain et al 2009, Seress et al 2012). These differences in reproductive success may be driven by changes in a range of environmental conditions, including temperature, food availability, nest predation, air pollution, and light pollution, but the precise nature of the mechanisms involved remain unclear (Gil and Brumm 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Peregrines in urban environments across Great Table 2 Britain were more successful than those in rural environments in terms of number of fledglings and nesting success. Indeed, the success of urban peregrine nests in this study (94 %) is the highest reported for any urban raptor species (Kettel et al 2018), or for rural peregrines in GB and elsewhere (e.g. Crick and Ratcliffe 1995;Amar et al 2012;Burke et al 2015).…”
Section: Discussionmentioning
confidence: 54%
“…Kettel et al (2018) highlight that while the breeding performance of small mammaleating raptors tends to be reduced in urban environments (e.g. Tella et al 1996;Liven-Schulman et al 2004;Charter et al 2007), the opposite is true for bird-eating raptors (e.g.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation